IMAGINATIONS OF DIFFERENT ANIMALS IN THE SYSTEM OF THE TRADITIONAL WORLD OUTLOOK OF UZBEK FOLK (Scientific journal of the Fergana State University, 2023)
The given article deals with the issues of snake cult in Ferghana Valley. Snake has a special place in belief of people, which was kept in  some rituals. Author analyzed modern views and beliefs of local people